HISTORY OF THE AVAR PRESS 1917-1930: THE FORMATION AND DEVELOPMENT - Malamagomedov, Dzamaludin Murtazalievic (History, Archeology and Ethnography of the Caucasus, 2019)
Like any social phenomenon, the press also has its own history and develops according to the objective laws of its development. Prior to the advent of the printing press and book printing, books were distributed through the creation of hand-written copies. At a certain stage of the development of society, there was a need for a printed word, and as a result, the first lithographs and printing presses appear. The origin and formation of the periodical press in the languages of the peoples of Dagestan is the result of the socioeconomic and political development of society. At the beginning of the 20th century, the first prerequisites for the appearance of printed materials in the languages of the peoples of Dagestan were born in Dagestan. Despite the new state system, the peoples of Dagestan still gave preference to the Arabic graphics and with the help of this letters continued to write, and it is no coincidence that the first Dagestani newspapers were published on the basis of this alphabet. The new Soviet state made every effort to create the national Dagestani press. If the Arabic periodicals of the period of the revolution and civil war in other languages of the peoples of Dagestan, in particular, in Kumyk and Lak, have been studied in part, then the publications in the Avar language however, have not been practically studied and introduced into scientific circulation. Moreover, most of them are still not identified, and there is no information on the number of such publications, let alone the content of newspaper articles. In this connection, the paper attempts, for the first time, to introduce into the scientific circulation newly discovered Arabic newspapers in the Avar language. The history of the formation and development of the periodical press in Dagestan is considered, and printed publications in the Avar language are studied through the prism of the Dagestan periodicals. The objective of the study is identification, paleographic characteristics and a general overview of the currently obtained Arabic periodicals in the Avar language.